Artificial Life and the Loss of Biodiversity: Ecological Consequences of Genetic Experiments in Oryx and Crake - Ms. A. Sri Sivabagya (International Journal of Scientific Research in Science and Technology, 2024)
Literature serves as a social representation. It represents the people, their inventions, and their environmental consequences. The Canadian writer Margaret Atwood’s Oryx and Crake is a dystopian novel that explores a world where corporate greed and scientific pride have collapsed the environment and replaced natural biodiversity with genetically modified beings. Genetic engineering has become both a wonder and a threat, raising intense ethical and existential questions in the contemporary world. The narrative moves along with the character Snowman, possibly the last human survivor in the apocalyptic world, who reflects on the consequences of experimentation on genetic modifications, especially by his friend Crake. It also explores the diverse genetic modifications the profit-driven corporate society has crafted, devoid of moral constraints. The novel through its hubris and ethical blind spots, critiques the human tendency to play the role of God by controlling nature without considering its consequences. This paper examines Atwood’s cautionary depiction of genetic engineering and highlights the novel’s warning about the need for ethical boundaries and regulatory supervision in scientific endeavors through an ecocritical perspective.
Keywords: Ecosystem; Genetic Modification; Nature; Environment; Artificial life; ecocriticism